(untitled) (World Bulletin of Social Sciences, 2026)
The article presents a scholarly study of the genealogy of the Holy Family in Christian and Islamic traditions. It analyzes the genealogies in the Gospels of Matthew and Luke, their differences, numerical structures, and theological aims. Special attention is given to the role of women in Matthew’s lineage. The Islamic perspective is represented through the family of Imran, and the Quranic portrayal of Mary and Jesus. The study draws on classical and modern sources, including works by Brown, Bryan, Muretov, and others. Using textual, historical-critical, and comparative methods, it reveals the symbolic and theological meaning and interfaith parallels in Holy family’s lineage.